Organizing Library Intrapreneurship - CHATTERJEE, Sidharta; SAMANTA, Mousumi (Journal of Advanced Research in Management; Vol 12 No 1 (2021): JARM Volume XII Issue 1 (23) Summer 2021DO - 10.14505//jarm.v12.1(23).02, 2021)
Libraries occupy a special space in our society, and our minds. Today, public libraries are struggling hard to attract new users and increase footfalls that seem to be in the downtrend. Besides, Physical Libraries need innovations in their services frontier to survive stiff competition from virtual digital libraries that provide instant access to information at no cost. Librarians and library professionals as knowledge managers could help design and foster entrepreneurship models of service delivery aimed towards bringing novelty in their operations. This is for the reason that libraries must take up the challenges to survive and compete with digital libraries which would maximize user satisfaction, attract new patrons and increase their user base. To make libraries economically independent and socially competent knowledge organizations, libraries need to innovate and adopt entrepreneurship-intrapreneurship business models which would attract investments from the private sectors. To transform libraries into productive, innovative knowledge organizations, librarians must take the initiative to think out of the box. This paper addresses these issues and analyses the intrapreneurship attitude to library operations. It argues that librarians should adopt a model of knowledge entrepreneurship where librarians, besides being knowledge managers, would also act as intrapreneurs within their organization.